Dual-career student athletes in Spanish universities: characteristics and interests - Hernando Domingo, Carlos; Renau-Michavila, Marta; Marín Gil, María Pilar (Frontiers in Sports and Active Living, 2025)
The path that student-athletes follow to pursue their dual careers is both complex and demanding. However, an increasing number of elite athletes enroll in higher education today. To explore the current situation of elite university athletes in Spain, a study was conducted with the main objective of identifying their characteristics, concerns, interests, and challenges when combining their sporting and academic careers. To this end, a survey consisting of 27 items was distributed among a group of Spanish universities belonging to the Spanish University Sports Committee. A total of 563 responses were collected, of which 411 were ultimately processed from 27 different Spanish universities, providing us with insight into pursuing a dual career in Spanish universities. Descriptive data were gathered on various aspects such as age, field of study, hours dedicated to sports and studies, sports level, most relevant sports disciplines, interest in transnational mobility, and the perception and use of the benefits student-athletes receive when pursuing a dual career. Ultimately, this work aims to assist higher education institutions in developing tools that facilitate the program design for elite athletes.